Dynamic user management model in interactive networked collaborative environment / Siti Zaleha Zainal Abidin … [et al.] - Zainal Abidin, Siti Zaleha; Omar, Nasiroh; Idrus, Zainura; Idrus, Zanariah (Research Management Institute (RMI), 2012)
Interactive networked collaborative virtual environment (NCVE) provides ways for people to work together, faster and cheaper despite of locations. Results can be achieved without travelling time and spending more money. Unfortunately, users' existence is not visibly presence which results in lacking of user participation that seriously degrades communication quality. This leads to misinterpretation of vital information and jeopardize the group work. Therefore, it is crucial to present users so that others know with whom they are interacting with (presence), when to communicate (state) and what to do (role) during the collaboration. This research investigates the activities of users in order to identify all the possible job functions exist during collaboration. Then, their job functions are classified in relation to the management of dynamic invisible users (their presence, states and roles). The users' role, presence and state will be generalized to form a generic management model of dynamic users based on logical notation. This work employs data collection through literature review and a case study. For a case study, a monopoly game will be implemented by changing some of its rules to gather all the possible roles exist throughout the game. The game is also used as a platform to do an abstraction of real life phenomena. A mapping of users' job functions found in both literature review and the case study will be conducted to produce comprehensive elements for managing users in collaborative systems. All the elements and their relations are classified and represented as a set of mathematical equations. The model helps to manage users dynamically throughout the collaborative session. This session-based dynamic role feature is rarely found in any collaborative work as compared to application-based role. Furthermore, managing users in virtual space is challenging because it involves security, privacy and permission to information resources.